The Importance of Iron in Pathophysiologic Conditions - Raffaella Gozzelino (Frontiers Research Topics, 2015)
The iron element (Fe) is strictly required for the survival of most forms of life, including bacteria, plants and humans. Fine-tuned regulatory mechanisms for Fe absorption, mobilization and recycling operate to maintain Fe homeostasis, the disruption of which leads to Fe overload or Fe depletion. Whereas the deleterious effect of Fe deficiency relies on reduced oxygen transport and diminished activity of Fe-dependent enzymes, the cytotoxicity induced by Fe overload is due to the ability of this metal to act as a pro-oxidant and catalyze the formation of highly reactive hydroxyl radicals via the Fenton chemistry. This results in unfettered oxidative stress generation that, by inducing protein, lipid and DNA oxidation, leads to Fe-mediated programmed cell death and organ dysfunction. Major and systemic Fe overloads occurring in hemochromatosis and Fe-loading anemias have been extensively studied. However, localized tissue Fe overload was recently associated to a variety of pathologies, such as infection, inflammation, cancer, cardiovascular and neurodegenerative disorders. In keeping with the existence of cross-regulatory interactions between Fe homeostasis and the pathophysiology of these diseases, further investigations on the mechanisms that provide cellular and systemic adaptation to tissue Fe overload are instrumental for future therapeutic approaches. Thus, we encourage our colleagues to submit original research papers, reviews, perspectives, methods and technology reports to contribute their findings to a current state of the art on a comprehensive overview of the importance of iron metabolism in pathophysiologic conditions.